Icings of the Indigirka river basin according to the recent Landsat satellite images and historical data - О. M. Makarieva; A. N. Shikhov; A. A. Ostashov; N. V. Nesterova (Лëд и снег, 2019)
The paper presents methods and results of creation of the digital catalogue of aufeises for the Indigirka river basin made on the basis of Landsat images and historical data. The region under study is the basin before the hydrometric section of GMS Vorontsovo, its area is about 305 000 km2. Historical data were taken from the Inventory of naleds of the North-East of the USSR territory published in 1958 and topographic maps. It includes the estimated coordinates and characteristics of 897 aufeises with total area of 2064 km2. The Landsatbased identification of aufeises for 2013–2017 allowed making description of 1213 aufeises over a total area of 1287 km2. The integrated digital catalogue of the aufeises for the Indigirka river basin based on combination of the above two sources is available at https://issues.pangaea.de/browse/PDI-17699. 10% of the largest aufeises make up about 60% of the total area of all aufeises according to both sources. The largest number of aufeises is at altitudes of 900–1300 m. The interannual variability of area of the aufeises for the period 2001-2016 was estimated by the example of the Bolshaya Momskaya naled and the group of large aufeises in the basin of the Syuryukty River which is the left tributary of the Indigirka. The conclusions cannot be considered unambiguous due to certain limitations of the imagery data but the results of the analysis is indicative of a tendency to decreasing in the area of the Bolshaya Momskaya naled in recent years, while no reduction in the aufeis area is noted in the basin of the Syuryukty River. The main results of this work are the new geodatabase of the aufeises in the Indigirka river basin, and also the comparison of the satellite observations with historical data performed for two major naleds. It is established that the satellite-estimated total area of aufeises is 1.6 times less than in the Cadastre (1958). At the same time, it was found that more than 600 aufeises recognized by the Landsat images were absent in the Cadastre of 1958. This may suggest that either the Cadastre data is incomplete or that conditions of the aufeis can be significantly changed over the past 50 years.